2001
DOI: 10.1159/000048142
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Deficiency and Replacement

Abstract: In the human male, testosterone is the major circulating androgen. More than 95% of circulating testosterone is secreted by the testis with a production rate of 6–7 mg/day. The clinical effects of androgens are numerous, and testosterone deficiency is associated with a number of clinical abnormalities. Overt hypogonadism results in reductions in bone mineral density, alterations in body composition and effects on mood, aggressive behaviour, cognitive function, sexual function and several factors important for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 68 publications
1
51
0
2
Order By: Relevance
“…51,52,54,55,[74][75][76][77][78][79][80] The benefits of testosterone therapy for men are clear and considered standard practice. 50,57,81 In addition, the high prevalence of MetS in retired football players is important because lifestyle changes may reverse some of these findings and improve the cardiovascular and metabolic disease risks that are associated with MetS. Lifestyle changes to reduce weight with appropriate hormonal supplement in these former athletes may improve not only QoL, but also decrease disease risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,52,54,55,[74][75][76][77][78][79][80] The benefits of testosterone therapy for men are clear and considered standard practice. 50,57,81 In addition, the high prevalence of MetS in retired football players is important because lifestyle changes may reverse some of these findings and improve the cardiovascular and metabolic disease risks that are associated with MetS. Lifestyle changes to reduce weight with appropriate hormonal supplement in these former athletes may improve not only QoL, but also decrease disease risks.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56][57][58][59][60] In addition to poor QoL, both GHD and hypogonadism can contribute to decreased lean body mass, increased fat mass (in particular, visceral fat), and poor exercise capacity that further contribute to poor QoL, obesity, and MetS, increasing cardiovascular disease (CVD) risk. 51,54,57,[61][62][63][64][65][66][67][68][69][70] Studies have shown that MetS is associated with, and predicts the development of, low serum testosterone levels in men. 62,64,65,71 Five of 6 subjects with hypogonadism had MetS and obesity.…”
Section: Previous Studies On Postconcussive Hypopituitarismmentioning
confidence: 99%
“…Recent advances include the development of longer-acting intramuscular testosterone preparations, which offer more stable androgen levels with fairly infrequent injections. 88 Intramuscular depot injections of testosterone esters are widely used. We start testosterone replacement between 10 and 11 year, simulating normal puberty according to the child's psychological evaluation and height.…”
Section: Male Social Sexmentioning
confidence: 99%
“…A few prospective clinical trials, some cross-sectional studies, and experimental studies suggest that testosterone has a beneficial effect on the development of atherosclerosis or its clinical manifestations in men (34). Large prospective trials and intervention studies are needed to better assess the metabolic and cardiovascular benefits of testosterone.…”
Section: Figure 2-correlation Between Lower Concentrations Of F-tes (mentioning
confidence: 99%